Enhancing productivity and profitability of spring maize (Zea mays) in Uttarakhand’s Tarai region through effective weed management practices and irrigation scheduling - CHINYO, MUNNY; KUMAR, SANDEEP; SINGH, T P; CHANDRA, S; GOND, SURAJ (The Indian Journal of Agricultural Sciences, 2024)
A field experiment was conducted during the spring seasons of 2022 and 2023 at Norman E Borlaug Crop Research Centre, Govind Ballabh Pant University of Agriculture and Technology, Pantnagar, Uttarakhand to enhance maize yield and profitability. The experiment was conducted a split-plot design (SPD) with two irrigation scheduling treatments, viz. irrigation applied at an IW/CPE ratio of 0.8 (I1); and 1.2 (I2) in main plot and 8 weed management treatments, viz. W1, atrazine 1000 g/ha; W2, tembotrione 120 g/ha; W3, topramezone 25.2 g/ha; W4, atrazine 1000 g/ ha followed by hand-weeding at 35 DAS (days after sowing); W5, atrazine 1000 g/ha followed by tembotrione 120 g/ha; W6, atrazine 1000 g/ha followed by topramezone 25.2 g/ha; W7, weed-free; and W8, weedy check in sub-plots. Irrigation applied at IW/CPE ratio of 1.2 significantly improved the maize productivity and profitability, yielding higher net returns (₹66,206.9/ha) and grain yield (6.1 t/ha). Among the herbicidal treatments, atrazine 1000 g/ha followed by topramezone 25.2 g/ha recorded the highest weed control efficiency (80%) and maize grain yield (6.3 t/ ha). The percentage net monetary return was in the following sequence: W6 (100%) > W7 (92.4%) > W5 (91.8%) > W4 (89.6%) > W3 (81.5%) > W2 (78.2%) > W1 (67.6%) > W8 (46.4%). The percentage gain in grain yield was recorded in the following sequence: W7 (100%) > W6 (91.4%) > W5 (87.4%) > W4 (86.4%) > W3 (84.1%) > W2 (81.1%) > W1 (71.5%) > W8 (52.5%). In conclusion, optimizing irrigation to IW/CPE ratio of 1.2 and employing weed management practice atrazine (1000 g/ha) followed by topramezone (25.2 g/ha) application, can significantly enhance spring maize yield, weed control efficiency and economic returns in Uttarakhand’s Tarai region.